ADAPTATION OF FOREIGN STUDENTS IN THE EDUCATIONAL PROCESS OF UNIV - Добротвор, О. В.; Щербина, І. Ю. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
This article is devoted to the study of the problem of integration of foreign students in the educational process of Ukrainian universities. The peculiarities of adaptation of foreigners in the new social environment are disclosed and ways of improving communication between students in the first days of their education in a new place are suggested. In particular, in the course of the study it was revealed that the training on knowledge of cultures and speech habits of representatives of different states helps foreigners to adapt more quickly and psychologically